Characteristics of endothelial dysfunction in patients with gout comorbid with arterial hypertension - Zolotariova, N. A.; Romanchenko, M. I.; Borovik, A. P. (Journal of Education, Health and Sport, 2016)
Zolotariova N. A., Romanchenko M. I., Borovik A. P. Characteristics of endothelial dysfunction in patients with gout comorbid with arterial hypertension. Journal of Education, Health and Sport. 2016;6(6):39-50. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54552 http://ojs.ukw.edu.pl/index.php/johs/article/view/3539 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. CHARACTERISTICS OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH GOUT COMORBID WITH ARTERIAL HYPERTENSION N. A. Zolotariova, M. I. Romanchenko, A. P. Borovik Odessa National Medical University, Odessa, Ukraine Abstract Currently there is scarce data on endothelial dysfunction (ED) in patients with gout (GA), moreover there are no current studies of ED in gout comorbid with arterial hypertension (AH). The purpose of this study is to describe specific features of biochemical and instrumental markers of endothelial dysfunction in patients with GA comorbid with AH. We measured and compared the level of Von Willebrand factor (vWF), interleukin-1beta (IL-1), endothelin-1 (ET-1), plasma nitrites (NO2-) and nitrates (NO3-), the total activity of NO-synthase, endothelium-dependent (FMD) and endothelium-independent vasodilatation (NMD) in 26 patients with GA, 26 patients with AH and in 86 patients with GA+AH. The study showed that vWF concentration was highest in comorbidity group (92,9±29,0%) showing no significant difference from GA and AH (79,2% and 86,5% respectively). IL-1 was highest in GA+AH group (2,0 pg/ml) being significantly higher than in AH (p=0,01) but showing no difference from GA (p=1,0). ET-1 concentration was highest in the comorbid pathology group (3,07 fmol/ml) versus 1,58 fmol/ml in GA (p<0,0001) and 2,77 fmol/ml in AH (p=1,0). NO-synthase activity was greatest in GA and in comorbid pathology groups showing no significant intergroup difference; NO2- and NO3- concentrations, being similar in these two groups, were statistically higher that in AH. Greatest reduction of FMD and NMD was found in comorbid pathology group (5,80% and 10,35% respectively) and it was not significantly different from AH group (6,18%; p=0,83 for FMD and 13,59%; p=0,079 for NMD). FMD and NMD in gout (10,03% and 15,35% respectively) were similar to normal, being significantly different compared to GA+AH group (p=0,045 for FMD and p=0,018 for NMD). This study shows that ED in gout is characterized by significantly higher concentration of IL-1, nitric oxide metabolites and intact FMD compared to hypertension. Hypertension is characterized by significantly higher concentrations of endothelin-1, more prominent increase in von Willebrand factor and significant FMD reduction. Endothelial dysfunction in comorbid pathology demonstrates "summation" of pathogenetic mechanisms of underlying disorders, expressed in significant increase of interleukin-1 and endothelin-1 concentrations, hyperactivation of NO synthesis together with decreased FMD and NMD. Keywords: hypertension, gout, endothelium, comorbidity.